Analysis of Population Immunity to Tick-Borne Encephalitis Virus in the Sverdlovsk Region - V. A. Mishchenko; I. P. Bykov; N. G. Popkova; A. M. Orlov; I. V. Vyalykh (Эпидемиология и вакцинопрофилактика)
Relevance. The study of population immunity to the tick-borne encephalitis virus in endemic areas helps to identify the circulation of the virus, makes it possible to assess the dynamics of the activity of natural foci and determine the area of distribution of the virus.The aim of this work was to analyze the level of population immunity to the tick-borne encephalitis virus in the Sverdlovsk region.Materials & Methods. Blood plasma from the adult working population (blood donors) was examined for the presence of specific IgG antibodies to the tick-borne encephalitis virus by ELISA during 2019-2021 in five municipalities of the Sverdlovsk region, located in different landscape and geographical zones. An antibody titer of 1:800 or higher was considered protective. A statistical analysis of the obtained data was carried out.Results. The number of individuals with a protective antibody titer in groups from various municipalities varied from 42.0 to 68.1%. Among persons who received revaccination over the past 3 years, IgG titers to TBEV of 1:800 and higher were determined in 79.8% of cases, when the vaccination period was from 3 to 6 years - in 61.3% of cases, and when the period from the last vaccination was more than 6 years – 47.5%. In the spring, specific antibodies in a protective titer were detected in 58.6% of those examined, in the fall they were detected in 55.1%. The data obtained confirm an age-dependent decrease in the level of humoral immunity to TBEV.Conclusions. The determining factor shaping the immune structure of the population in relation to tick-borne viral encephalitis is vaccination, and a significant role in the formation of population immunity must be given to the natural pro-epidemic of the population in endemic areas, as well as age characteristics. In conditions of mass immunization of the population against tick-borne encephalitis in endemic areas, it is rational to increase the interval between revaccinations using a personalized approach with preliminary determination of the level of specific IgG in the blood serum.